How can the cost and effectiveness of renewable portfolio standards be coordinated? Incentive mechanism design from the coevolution perspective - Xin-gang, Zhao; Yi, Zuo; Hui, Wang; Zhen, Wang (Renewable & sustainable energy reviews, 2022)
Renewable portfolio standards are essential means to promote the transition to low-carbon energy by encouraging obligated subjects to purchase tradable green certificates. However, the trade-off between Renewable portfolio standards' cost and effectiveness is a challenge for the government, because they want to support the development of renewable energy at the lowest cost. This paper constructs a coevolution model for a renewable energy system incorporating Renewable portfolio standards to explore how incentive mechanisms impact the cost and effectiveness of Renewable portfolio standards. The simulation results show that with the coevolution of the RE system, Renewable portfolio standards' effectiveness gradually rises; concurrently, its cost increases first before later decreasing. However, the path-dependence of the behavioural evolution of the tradable green certificate market players hinders further improvements in Renewable portfolio standards' cost-effectiveness. In addition, high quotas and price collars close to TGC value improve the cost-effectiveness, whilst the sloped penalty mechanisms, banking mechanisms with a valid period longer than one year, and borrowing mechanisms significantly reduce costs. On this basis, the government can design dynamic incentive mechanisms to guide the market players’ behavioural evolution and decrease costs whilst also ensuring effectiveness. •The effectiveness of Renewable portfolio standards (RPS)gradually rises.•The cost of RPS first increases and then decreases.•Higher quota and price collars close to value improve the cost-effectiveness of RPS.•Penalty, banking and borrowing mechanisms can reduce the cost of RPS.